Consultant characteristics in sport psychology service provision: A critical review and future research directions. Issue 1 (2nd January 2020) - Woolway, Toby; Harwood, Chris G.
Abstract : The sport psychology consultant's (SPC) first impression and rapport building with potential clients is vital to "gaining entry" – the precursor to subsequent service provision. Understanding those characteristics of the consultant that influence the clients' preference and likelihood to seek psychological services contributes to the development of educational training programmes for neophyte practitioners, and marketing tools for the field as a whole. This article offers a critical review of studies that have investigated the preferred characteristics of SPCs in terms of likelihood to seek services. A computerised literature search identified 17 studies representing a total of 2962 participants. The most preferred SPC was of the same gender, race, and age of the client with a high athletic background, sport-specific knowledge, and interpersonal skills. Such a consultant was lean and athletically built, physically active, possessed either an advanced degree or was certified and had experience working with diverse populations. Methodological and sampling limitations, as well as future research directions, are highlighted. SPCs and governing bodies are encouraged to consider these findings for training and marketing purposes.